Relevance of Artificial Intelligence in Marketing: A Narrative Review and Future Directives - Kotla Srikanth (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Technological innovations, for instance, Internet of Things, big data analytics, blockchain & Artificial Intelligence led to a paradigm shift in the ways the firms function. Amongst the total technological innovations, Artificial Intelligence is the contemporary innovation & acquires a huge marketing transformation competence. Theorists across the globe are striving to decipher the gold-standard Artificial Intelligence results for their marketing functions. Specifically, Artificial Intelligence agents led by machine learning formulas are significantly altering the marketing space, creating huge inquisitiveness from the empiricists. In the current paper, qualitative content review is done to analyze the secondary data sources and the findings of the content analysis resulted in an in-depth apprehension of Artificial Intelligence significance in the discipline of marketing. Deriving upon the evidence from the text analysis, the current paper provides a narrative review of the significance of Artificial Intelligence in the context of conventional marketing mix - product, price, place & promotion management. This article further uncovers the Artificial Intelligence driven marketing industry trends which include - interactive & media-enhanced, individualization & targeting, real-time optimization & computerization, and lastly consumer-journey attention. We then conclude with the future research directions of Artificial Intelligence & machine learning in the marketing context.